PEREMPUAN DALAM JERAT TERORISME: ANALISIS MOTIVASI PELAKU BOM BUNUH DIRI DI INDONESIA - Nur Kasanah (Institut Agama Islam Negeri Ponorogo, 2021)
Recent acts of terrorism have experienced a shift in perpetrators. If all this time women were only behind the scenes, now they have started to show themselves as main actors such as weapons providers, bomb builders and even suicide bombers. The women involved as perpetrators are actually victims of the snares of terrorism. This paper aims to analyze what are the motivations behind women who are entangled in the vortex of terrorism so that they are willing to become suicide bombers. The results of the study found at least six factors that caused women to be willing to become combatants, namely the occurrence of jihad indoctrination deviations, the lure of going to heaven, married by terrorist, discriminated feeling, frustrated feeling so that suicide bombing is a shortcut to repentance and revenge for being victims of sexual harassment.Key word: women; terrorism; suicide bombing